2007
DOI: 10.2527/jas.2006-324
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in BMPR-IB and BMP-15 genes are associated with litter size in Small Tailed Han sheep (Ovis aries)1

Abstract: The Small Tailed Han is a prolific local sheep breed in China. The bone morphogenetic protein receptor IB (BMPR-IB) gene, which affects the fecundity of Booroola Merino sheep, and the bone morphogenetic protein 15 (BMP-15) gene, which affects the fecundity of Inverdale, Hanna, Belclare, Cambridge, and Lacaune sheep, were studied as candidate genes associated with the prolificacy of Small Tailed Han sheep. Single nucleotide polymorphisms of BMPR-IB and BMP-15 genes were detected in Small Tailed Han ewes (n = 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
126
4
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(154 citation statements)
references
References 18 publications
11
126
4
13
Order By: Relevance
“…Although a mutation in the BMPR1B gene has been identified in several sheep lines selected for increased fecundity (Davis et al 2002, Chu et al 2007, the same mutation (Mulsant et al 2001, Souza et al 2001, Wilson et al 2001 has been observed in each of these lines. In contrast to the relatively restricted expression of the GDF9 and BMP15 genes, BMPR1B is widely expressed throughout the body and the mutation likely subtly affects multiple tissue types including the pituitary and the adrenal glands (Wilson et al 2001, Xu et al 2010).…”
Section: Bmpr1b Mutationmentioning
confidence: 90%
See 1 more Smart Citation
“…Although a mutation in the BMPR1B gene has been identified in several sheep lines selected for increased fecundity (Davis et al 2002, Chu et al 2007, the same mutation (Mulsant et al 2001, Souza et al 2001, Wilson et al 2001 has been observed in each of these lines. In contrast to the relatively restricted expression of the GDF9 and BMP15 genes, BMPR1B is widely expressed throughout the body and the mutation likely subtly affects multiple tissue types including the pituitary and the adrenal glands (Wilson et al 2001, Xu et al 2010).…”
Section: Bmpr1b Mutationmentioning
confidence: 90%
“…The AA genotype had a larger litter size than the AB genotype, suggestive of higher ovulation rates in the homozygous vs the heterozygous carriers. However, interpretation of these data sets is complicated by the lack of any animals with the BB genotype, potentially due to the rarity of the B allele, and the knowledge that mutations in both BMP15 and BMPR1B are also present, but not fixed, in the Small Tailed Han sheep (Davis et al 2006b, Chu et al 2007). …”
Section: Gdf9 Mutationsmentioning
confidence: 99%
“…New findings indicated that multiple births in sheep bearing the Booroola gene (FecB) are a result of chromosome 6 mutation in a part comprising bone morphogenic protein receptor gene IB (BMPR-IB) (1,4,(13)(14)(15). The BMPR-IB gene encodes the morphogenic growth factor ÎČs.…”
Section: Introductionmentioning
confidence: 99%
“…In general, heterozygous ewes with mutations in both FecB and FecX G exhibited increased fertility compared with ewes harboring a mutation in only one of these genes [6] . The Galway mutation has been identified in Cambridge [16] , Garole, Kendrapada [12] and Small Tailed Han sheep [19] . Hanrahan et al [16] estimated the effect of FecX G to be 0.77 and 1.18 in Belclare and Cambridge ewes, respectively.…”
Section: Introductionmentioning
confidence: 99%